2021
DOI: 10.3390/pharmacy9010027
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Analysis of Online Reviews for Selective Serotonin Reuptake Inhibitors and Serotonin–Norepinephrine Reuptake Inhibitors

Abstract: Background: Depression affects millions worldwide, with drug therapy being the mainstay treatment. A variety of factors, including personal reviews, are involved in the success or failure of medication therapy. This study looked to characterize the sentiment of online medication reviews of Selective Serotonin Reuptake Inhibitors (SSRIs) and Serotonin–Norepinephrine Reuptake Inhibitor (SNRIs) used to treat depression. Methods: The publicly available data source used was the Drug Review Dataset from the Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Hence, patient reviews of these psychiatrists may not represent the full spectrum of patient perceptions of different forms of psychiatric care, either in the United States or abroad. Nevertheless, the 6,400 patient reviews examined in this sample nevertheless are on par with the sample size found in other sentiment analysis studies of patient reviews in mental healthcare (12). Given today's accessibility of different publicly available physician rating websites across the globe, future studies may extend this approach by including other physician rating platforms and identifying common attributes of psychiatrists that positively shape patients' perception of psychiatrists.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Hence, patient reviews of these psychiatrists may not represent the full spectrum of patient perceptions of different forms of psychiatric care, either in the United States or abroad. Nevertheless, the 6,400 patient reviews examined in this sample nevertheless are on par with the sample size found in other sentiment analysis studies of patient reviews in mental healthcare (12). Given today's accessibility of different publicly available physician rating websites across the globe, future studies may extend this approach by including other physician rating platforms and identifying common attributes of psychiatrists that positively shape patients' perception of psychiatrists.…”
Section: Discussionmentioning
confidence: 87%
“…Sentiment analysis is a machine learning-based technique for rating positive or negative use of language in text that recently led to an increased understanding of clinical contributors to patient satisfaction in surgical fields (10,11). In the field of psychiatry, previous studies have demonstrated the validity of sentiment analysis among antidepressant users and for online mental health consultation services (12,13). Specifically, while the general attitude toward online mental health consultation services and the usefulness of online reviews in China have previously been examined, no studies to date have elucidated impactful attributes of psychiatrists that can improve patient experiences during their mental health visits in the United States using PRWs (13).…”
Section: Introductionmentioning
confidence: 99%
“…The AFINN tool has been used to analyze the sentiment included in tweets about Asperger [ 5 ], and to compare the sentiment towards different COVID-19 vaccines expressed in social media posts [ 27 ]. The AFINN tool has also been used to analyze free short text, such as answers given in surveys [ 28 , 29 ], web-based reviews [ 30 ], self-reported notes [ 31 ], or descriptions of public health campaigns [ 32 ].…”
Section: Methodsmentioning
confidence: 99%